Metabolic Profiling and Gene Expression Analyses of Purple-Leaf Formation in Tea Cultivars (Camellia sinensis var. sinensis and var. assamica) - Zhu, Ming-zhi; Zhou, Fang; Ran, Li-sha; Li, Yi-long; Tan, Bin; Wang, Kun-bo; Huang, Jian-an; Liu, Zhong-hua (Frontiers in Plant Science, 2021)
Purple-leaf tea cultivars are known for their specific chemical composition that greatly influences tea bioactivity and plant resistance. To better understand the mechanisms underlying purple-leaf formation, we analyzed the accumulation and biosynthetic regulation of three pigments (chlorophylls, carotenoids, and anthocyanins/flavonoids) in four purple-leaf tea cultivars by integrated metabolic and gene expression analyses. Two were bred by our team and three were analyzed for the first time. Green-leaf and yellow-leaf cultivars were employed for comparison. The purple-leaf phenotype was mainly attributed to anthocyanin accumulation and low chlorophylls. The purple-leaf phenotype led to other flavonoid changes including lowered monomeric catechin derivatives and elevated polymerized catechin derivatives. Gene expression analysis revealed that 4CL, ANS, and UFGT genes in the anthocyanin biosynthetic pathway and the HEME gene in the chlorophyll biosynthetic pathway were responsible for high anthocyanin and low chlorophyll, respectively. These findings provide insights into the mechanism of purple-leaf formation in tea cultivars.